The Effect of Gamma Ray Radiation on the Growth of Local Rice Plants (Oryza sativa L.) Silumat Variety - Danu Lesmana; Siti Hartati Yusida Saragih; Ika Ayu Putri Septyani; Yusmaidar Sepriani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice is a staple food and a primary ingredient for many communities. The available rice supply is expected to meet the growing demand. This study aims to investigate the effects of gamma-ray radiation on the growth of rice plants of the Silumat variety and to determine the optimal gamma-ray radiation dose for their growth. The research employs an experimental method using a non-factorial Randomized Block Design (RBD) with 10 treatment levels: R0 = Control (No Radiation), and radiation doses of 50, 100, 150, 200, 250, 300, 350, 400, and 450 Grey. The results showed that gamma radiation significantly affected the viability, plant height, and number of tillers in the local rice variety Silumat (Oryza sativa L.). Low doses, particularly 50 Gy and 100 Gy, exhibited a stimulating effect (hormesis), enhancing germination, plant height, and tillering. In contrast, higher doses (>150 Gy) tended to reduce all parameters due to physiological and genetic damage. This study provides specific information on the optimal gamma radiation dose range to stimulate the growth of the Silumat variety, which can serve as a reference for plant breeding programs based on induction treatment.